América latina: des-integración económica, territorios y conflictos - Hernandez, Olmedo Vargas; Rojas, Ahiliz (Universidad Pedagógica y Tecnológica de Colombia, 2008)
Abstract: As an inter-territorial borders are becoming less important in the dynamic economic, political and cultural relations, which stimulates the globalization of capital, with its various forms of globalization, Latin American countries fail to make progress in the integration processes intraregional economic or global level, because the system of external relations defined by the states of these countries are still subject to defining their territorial boundaries, from Mexico to Patagonia, in an atmosphere of tension and confrontation permanent, destabilizes all processes and projects for Community action, as opposed to the great challenges of global economic and technological development.